The Water & Conflict Podcast, with CGIAR - Episode 1 - International Water Management Institute (International Water Management Institute, 2024)
Brought to you by IWMI and Dinovate, join your hosts Christine Akume David and Bunmi Afolabi for episode one as they chat to IWMI’s Adebayo Oke, Regional researcher for agricultural water solutions, and Dinovate’s Oluseyi Abdulmalik, Strategic Communiations Lead.